Three-dimensional interferometric stage encoder using a single access port - Wiseman, Kieran B.; Kissinger, Thomas; Tatam, Ralph P. (Elsevier, 2020)
We present a novel multi-dimensional positional encoder approach that uses range-resolved interferometry (RRI) to simultaneously interrogate multiple interferometers differing in optical path length, using only a single photo detector and a single diode laser. Employing only stage-mounted non-polarising beamsplitters and reflections from three orthogonal, externally mounted, planar mirrors, three Cartesian measurement directions are formed, that when combined with measurements from a stage-mounted reference reflection, allow for three-dimensional measurements of stage motion obtained via a single access port. Through a variety of movements of a three-dimensional Piezo-electric stage over its nominal stage working range of ± 50 μm, simultaneous measurements of displacements from three orthogonal dimensions are acquired with a 10 kHz quadrature bandwidth, achieving typical displacement noise densities of below 0.4 nm/√Hz with the noise floor dropping to below 0.1 nm/√Hz above 50 Hz, as well as high linearity with cyclic errors amplitudes well below 1 nm in all three directions.
Keywords: Displacement measurement; Range-resolvedinterferometry; Diode lasers; Dimensional metrology; Optical encoder; Interferometry